Кейс-метод як ефективна технологія вивчення національних і культурних особливостей бізнесу у вищих технічних навчальних закладах України - Лапузіна, Олена Миколаївна; Северин, Надія Василівна (ТОВ "Твори", 2020)
У статті проаналізовано проблему доцільності вивчення студентів вищих технічних навчальних закладів України основних правил бізнес-комунікацій із урахуванням національних особливостей представників різних країн світу. Описано типовий образ сучасного фахівця, що працює в глобальному оточенні, який має не тільки розробити продукцію, але й уміти презентувати її, зацікавити в перевагах її використання потенційних партнерів і покупців у всьому світі, що є виключно важливим для ефективної ділової співпраці. Проведено педагогічний експеримент, за результатами якого зроблено висновок про те, що використання кейс-методу за національними особливостями ділової етики стане вагомим інструментом для майбутньої ефективної діяльності технічних фахівців, а також для формування їхніх життєвих цінностей і толерантного світогляду.

The goal of the study is to show how university teachers can help students acquire knowledge and practical skills based on international and national business ethics. The problem of teaching the basic rules of business communication with national peculiarities at higher technical Ukrainian educational institutions is analyzed. A typical image of a modern specialist who has to not only develop products, but also present them for potential partners and customers around the world, which is extremely important for effective business cooperation in a global environment, is described. An online survey for determining the importance of knowledge in the field of national peculiarities of business communication and their impact on the success of business relations was conducted. A concept for the formation of practical skills in this sphere for future technical specialists based on the results of the survey among managers of joint international companies in Ukraine, as well as among students of the National Technical University “Kharkiv Polytechnic Institute” (NTU “KhPI”) was formed. Training materials and a package of business cases with national peculiarities of business communication were created. A strategy for studying using cases based on business ethics national peculiarities during university education is proposed. A pedagogical experiment was conducted. According to the results, the conclusion about effectiveness of proposed case method was made. It is stated that this method would become a significant tool for the future technical specialists’ effective work, as well as for their life values, tolerant worldview formation and responsible activities. The importance of higher education role in forming business ethical behavior with regard to national peculiarities is determined.
Case method as an effective technology of studying national and cultural features of business in the higher technical educational institutions of Ukraine
Keywords: кейси з ділової етики; національні особливості ділової етики; етика ділового спілкування; ділова співпраця; навички критичного мислення; національні особливості ділової етики; глобалізація економіки; бізнес-комунікації; business ethics cases; national features of business ethics; ethics of business communication; business cooperation; critical thinking skills; national features of business ethics; globalization of the economy; business communication